Self-healing of Covid-19 survivors in building communication with the surrounding environment - Nifta Alifatul Khotijah (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2022)
COVID-19 entered Indonesia in 2020. Many victims died due to COVID-19 causing excessive fear, which impacted social relations survivors COVID-19 and limited communication with the surrounding environment. This study aims to find out how the self-healing experience of patients recovering from COVID-19 and how patients recovering from COVID-19 build communication with the surrounding environment. This study uses a qualitative method with a phenomenological approach. Informants were selected using the purposive sampling technique. Methods of data collection using observation, interviews, and documentation. The data analysis technique uses the IPA (Interpretative Phenomenology Analysis) method using the source triangulation data validation method. The results are self-healing using the power of the mind, exercise therapy, chest therapy, religious spiritual approach, self-healing with laughter, gratitude and introspection. Build communication with the surrounding environment by participating in congregational prayers at the mosque, greeting greetings, staying in touch with relatives, and participating in existing social activities. This is related to Alfred Schutz's phenomenological theory with motives that can be used to describe human or individual actions based on the experience of phenomena that have happened to someone, namely In-order-to-motive (Um-zu-Motive) and Because of motive (Weil